Hating America - Barry Rubin (Oxford University Press, 2004)
With this powerful work, the Rubins trace the paradox that is America, a country that is both the most reviled and most envied land on earth. In the end, they demonstrate, anti-Americanism has often been a visceral response to the very idea-as well as both the ideals and policies--of America itself, its aggressive innovation, its self-confidence, and the challenge it poses to alternative ideologies